Analisa Rancang Bangun Sistem Informasi Pengolahan Data Barang Dan Point Of Sales Menggunakan Metode Waterfall - Noprianto, Noprianto (Jurnal Sosial Teknologi, 2025)
Analysis and Design of an Information System for Inventory Data Management and Point of Sales The Inventory Data Management and Point of Sales System is an application designed to simplify the process of managing inventory data and cashier operations, particularly for administrators who also serve as business owners. Several problems are commonly encountered, such as inaccuracies in recording incoming goods, leading to discrepancies between recorded inventory data and the actual physical stock. Additionally, issues often arise at the cashier, including inconsistencies between sales reports and financial reports, which frequently cause operational challenges in the store. This research and system design utilize the PHP programming language and a MySQL database. System modeling is analyzed using the Unified Modeling Language (UML), while the Waterfall methodology is applied for system development. The interface is supported by Bootstrap, making it easier to create web pages. For testing, both White Box Testing and Black Box Testing approaches are used.